Coping Strategies in Egyptian Ladies with Breast Cancer. (January 2014) - Elsheshtawy, Eman A.; Abo-Elez, Warda F.; Ashour, Hala S.; Farouk, Omar; zaafarany, Maha I. Esmael El
Introduction: A diagnosis of breast cancer regardless of the stage can be stressful, impact multiple spheres of life, and disrupt physical status, emotional and spiritual well-being, and personal relationships for the patient and family. In order to adapt, the patient ought to employ certain coping mechanisms. Individuals with terminal illness who utilize coping strategies have better quality of life compared to those who do not. Patients and Methods: This study aimed to determine the strategies used by females with breast cancer to cope with such stress by using Brief COPE scale and the hospital anxiety and depression scale. The study included 56 female patients diagnosed with operable breast cancer at Mansoura Oncology Center before surgery. Results: Large proportion of patients used acceptance, religion, and emotional support in coping with the stress of having breast cancer. Patients with depressive symptoms scored significantly higher venting while those with anxiety scored higher positive reframing, planning, and venting. Conclusion: Efforts should be made to encourage women with breast cancer to use coping strategies that have been found to be helpful (eg, acceptance, emotional support, distraction, and active coping strategies).